A novel phosphorus/nitrogen-containing liquid acrylate monomer endowing vinyl ester resin with excellent flame retardancy and smoke suppression. (20th October 2020) - Ji, Sa; Duan, Huajun; Chen, Yongsheng; Guo, Dingcheng; Ma, Huiru
Abstract: In this work, a liquid acrylate monomer (PHT) derived from phosphate and triazine-trione groups was successfully synthesized by the nucleophilic substitution reactions among phenyl dichlorophosphate (PDCP), 2-hydroxyethyl methacrylate (HEMA) and 1, 3, 5-tris(2-hydroxyethyl)isocyanurate (THEIC). The chemical structure of PHT was detailedly characterized by fourier transform infrared (FTIR) spectrum and 1 H as well as 31 P nuclear magnetic resonance (NMR) spectra. Then a series of flame-retardant vinyl ester resin (VER) thermosets were prepared by the radical copolymerization of PHT and the commercial 901-VER. The test results of limited oxygen index (LOI) and cone calorimeter indicated that the introduction of PHT greatly improved the fire-retardant performance and smoke suppression of 901-VER. Especially, the fire-retardant VER exhibited the best flame retardancy when the addition amount of PHT was 15 wt%. In this case, the LOI value of the as-prepared VER increased from 19.5% of 901-VER to 29.0%, and its peak heat release rate (pk-HRR), total heat release (THR), total smoke production (TSP) as well as average effective heat of combustion (av-EHC) values were respectively decreased by 39.3%, 20.7%, 31.9% and 31.5% compared with those of neat 901-VER. In addition, from the analyses of char residues after cone calorimeter tests and pyrolysis products of PHT, it can be concluded that PHT can play a flame retardant effect in both condensed phase and gas phase, especially the quenching and dilution effects in the gas phase, thereby imparting good flame retardancy to 901-VER.This study expands the application of VER in the fields with flame-retardant requirements. Graphical abstract: Image 1 Highlights: A liquid acrylate monomer containing phosphate and triazine-trione was synthesized. It greatly enhanced the fire safety and smoke suppression of VER. It can exert the quenching as well as dilution effects in the gas phase.